PENGARUH JUMLAH ANGGOTA LEGISLATIF TERHADAP KINERJA NON KEUANGAN, DIMEDIASI MANDATORY SPENDING - Sunardi Sunardi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This study aims to examine the direct and indirect effects of the number of legislative members on mandatory spending on education and health spending and their impact on non-financial performance (junior high school enrollment rates and community services with health workers). The population in regency and municipal governments in Southern Sumatra, from 2016 to 2018, brings up 174 observations. Testing using regression and path analysis. The results showed that the direct effect of the number of legislative members on mandatory spending on education and health spending was positive and significant, the effect of mandatory spending on education and health spending on the enrollment rate of junior high school and community services with health workers was positive and significant. Furthermore, the direct and indirect effect of the number of legislative members on the Junior High School Net Enrollment Rate is positive and significant, while the direct effect of the number of legislative members on community services with health personnel is negative, but the indirect effect is positive. Furthermore, the direct and indirect effect of the number of legislative members on the Junior High School Net Enrollment Rate is positive and significant, while the direct effect of the number of legislative members on community services with health personnel is negative, but the indirect effect is positive.